Perspectives of Armenian: Iranian economic relations within Belt and Road Initiative - Karen Grigoryan; Ali Arpanahi (OrdnungsPolitisches Portal (OPO), 2022)
Armenia-Iran North South Transport corridor is vital for Iran and Armenia and also for all parties involved. Recently, India increased its interest in Armenia and would like to see the INSTC passing through the Armenian territories, keeping in mind that Armenia is also the only country in the EAEU that has a land border with Iran. Taking into account Iran's desire to become a full member of the EAEU in the future, as well as India's interest in the EAEU structure and possible future membership, Armenia's chances of joining regional trade projects would be high. North South Transport Corridor route via India, Iran, Armenia, Georgia and Russia. This route is 30% cheaper and 40% shorter than the current traditional route. A country with a small domestic market like Armenia, of course, needs to expand its economic and trade ties with other countries in the world. The "One Belt, One Road" initiative can provide such an opportunity. An opportunity will also be created for the development of the Armenian transport infrastructure. Armenia aimed to construct the "North-South" transport road, 550-km long, to facilitate communication with Iran and Georgia and beyond.
Keywords: 330; Belt and Road Initiative; Armenia; Iran; China; India; trade; transport infrastructure; Silk RoadRoute